Integration of emotional intelligence in teaching practice among university teachers in higher education - Mamat, Norul hidayah (Universiti Utara Malaysia Press, 2021)
Emotional intelligence abilities of university teachers are more likely to establish suitable emotional teaching and learning environments through their teaching practice, thus promoting learning motivation and engagement among students. Despite the emphasis on the importance of teachers’ emotional intelligence abilities in teaching, it continues to be under-acknowledged and underdeveloped. This is evidenced in a few studies reported on the relationship between emotional intelligence and teaching practice particularly in higher education. Guided by the Four-Branch Emotional Intelligence Ability Model, this study aimed to explore the integration of emotional intelligence in teaching practice among university teachers in higher education.